PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING UNTUK MENGURANGI FREKUENSI BERMAIN GADGET PADA SISWA SEKOLAH DASAR - Diana Dewi Wahyunigsih; Eny Kusumawati (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
Advances in technology in this modern era, make small children begin to shift from real or physical games to fictional or unreal games that are packaged in a gadget. Kid's addiction to gadgets needs to be anticipated. The aim to be achieved in this study is to determine the effect of the application of group guidance services with role playing techniques to the frequency of playing gadgets on elementary school students in Mojolaban Subdistrict, Sukoharjo.The method used in this research is kuantitatif. The experimental design used is the One-Group Pretest-Posttest Design. Based on the results of the study, it is known the result of the frequency of playing gadgets can be reduced through group guidance services with role playing techniques in elementary students in Mojolaban Subdistrict Sukoharjo. This is evidenced from the results of data analysts using the T-test where a significant value of 0.000 <0.05 is obtained, so it can be concluded that there is a significant difference between the results of the pretest and posttest values. These results indicate that Ho was rejected and Ha was accepted. Thus it can be stated that group guidance services with role playing techniques influence the frequency of playing gadgets in elementary school students in Mojolaban Subdistrict Sukoharjo 2020/2021 school year.